1C.06: AMBULATORY PULSE PRESSURE IS NEGATIVELY ASSOCIATED WITH EXCRETIONS OF URINARY CAFFEINE AND ITS METABOLITES. (June 2015) - Guessous, I.; Pruijm, M.; Ponte, B.; Ehret, G.; Ansermot, N.; Vuistiner, P.; Staessen, J.A.; Gu, Y.M.; Paccaud, F.; Mohaupt, M.G.; Vogt, B.; Pechère-Berstchi, A.; et al.
Abstract : Objective: Systolic blood pressure (BP) has been associated with urinary caffeine and its metabolites such as paraxanthine and theophylline. Caffeine and caffeine metabolites could influence arterial pulse pressure (PP) via sympathomimetic effects, smooth muscle relaxation, and phosphodiesterase inhibition. The purpose of this analysis was to explore the association of ambulatory PP with urinary caffeine and its related metabolites in a large population-based sample. Design and method: Families were randomly selected from the general population of three Swiss cities (2009–2013). Ambulatory BP monitoring was conducted using validated Diasys Integra devices. PP was defined as the difference between the systolic and diastolic ambulatory BP. Urinary caffeine, paraxanthine, theophylline, and theobromine excretions were measured in 24 h urine using ultra-high performance liquid chromatography tandem mass spectrometry. Urinary excretions were log-transformed to satisfy regression assumptions. We used linear mixed models to explore the associations of urinary caffeine and caffeine metabolite excretions with 24-hour, day- and night-time PP while adjusting for major confounders. Results: The 836 participants (48.9% men) included in this analysis had mean (±SD) age of 47.8 (±17.5), and mean 24-hour systolic and diastolic BP of 120.1 mmHg (±13.9) and 78.0 (±8.6). Except theobromine, log transformed urinary caffeine and caffeine metabolite excretions were associated negatively with 24-hour, daytime and night-time ambulatory PP. 24-hour, daytime, and night-time ambulatory PP decreased by −0.804 mmHg (SE, 0.209), −0.749 (0.215), and −0.968 (0.243) (all P values <0.005), for each doubling excretion of caffeine. Strong negative associations with night-time ambulatory PP were observed for paraxanthine and theophylline. Figure. No caption available. Conclusions: The negative associations of PP with caffeine, paraxanthine, and theophylline excretions suggest that caffeine and its metabolites do lower BP, possibly by modifying arterial stiffness.